The Wisconsin Alzheimer's Institute Dementia Diagnostic Clinic Network: A community of practice to improve dementia care. Issue 7 (1st April 2022) - Mora Pinzon, Maria; Krainer, Jody; LeCaire, Tamara; Houston, Stephanie; Green‐Harris, Gina; Norris, Nia; Barnes, Stacy; Clark, Lindsay R.; Gleason, Carey E.; Hermann, Bruce P.; Ramon, Helen; Buckingham, Will; et al.
Abstract: Background: The Wisconsin Alzheimer's Institute (WAI) Dementia Diagnostic Clinic Network is a community of practice formed in 1998 as a collaboration of community‐based clinics from various healthcare systems throughout the state. Its purpose is to promote the use of evidence‐based strategies to provide high quality care throughout Wisconsin for people with dementia. The purpose of this study is to describe the use of a community of practice to facilitate education of healthcare providers on best practices in dementia care, and the implementation of an interprofessional approach to diagnose and manage dementia and related disorders. Methods: Cross‐sectional study of the members of the WAI's Dementia Diagnosis Clinic Network. Characteristics of clinics and healthcare teams, learners' participation in educational events and educational outcomes were collected from evaluation forms. Number and characteristics of patients seen in the memory clinics were collected from de‐identified data forms submitted by members to a centralized location for data analysis. Results: The clinic network currently has 38 clinics affiliated with 26 different healthcare systems or independent medical groups in 21 of 72 Wisconsin counties. Most (56%) are based in primary care, 15% in psychiatry, and 29% in neurology. Between 2018 and 2021, we received data on 4710 patients; 92% were ≥65 years old, 60% were female, and 92% were white. Network members meet in‐person twice a year to learn about innovations in the field of dementia care and to share best practices. Educational events associated with the network are shown to be relevant, useful, and improve knowledge and skills of participants. Conclusion: Communities of practice provide added value via shared best practices and educational resources, continuing education of the health workforce, continuous quality improvement of clinical practices, and adoption of new diagnostic and management approaches in dementia care.